TRAFFIC ORGANISATION IN THE CLOSE NEIGHBORHOOD PREROV RAILWAY STATION (Perner's Contacts, 2010)
The paper deals with traffic organization in the close neighborhood Prerov railway station  The possible variants of improve traffic situation in this area and in the individual crossroads are propound by analyze of the present state current  In conclusion the variants are assessed and compare with.
Keywords: signalized intersection; uncontrolled crossroads; stream of traffic; traffic circle; intensity; capacity of crossroads; transportation survey